Next Generation of Advanced Non-Small Cell Lung Cancer Therapy: Targeted and Immuno-Therapies - Chan, Sze Wah Samuel; Smith, Elliot (International Journal of Medical Students, 2020)
Lung cancer is one of the deadliest cancers in the world. Current clinical trials are focused on developing the next generation of therapies that target novel anti-cancer mechanisms. One approach is to prime the immune system, as the cancer has been known to suppress immune cells in the tumour microenvironment. Using pharmacotherapy, the immune system can be unleashed and suppress the cancer’s growth. Another pathway is targeting known oncogenic genes that are important for the cancer’s growth and survival. In lung cancer, the epidermal growth factor receptor and several other mutated proteins are targets of small-molecule inhibitors that have been shown to drastically improve patient survival and quality of life. Discussed in this review are broad highlights of the different immunotherapies and small molecule targeted therapies that have been studied in the latest clinical trials for lung cancer.